Typhoon and agricultural production portfolio: Empirical evidence for a developing economy - Thi Xuyen Tran (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2021)
In this paper, we investigate whether and how households adjust their agricultural practices such as cultivation and livestock to adapt to a severe typhoon.We, therefore, make use of a natural experiment coming from the strong typhoon Ketsana in 2009. We apply the difference-in-differences approach using micro-data on household level and spatial data of this severe typhoon. Our empirical findings suggest that households alter their agricultural activities in response to a strong typhoon. While they decrease the crops-planted area, they tend to purchase more livestock in the short term and in the medium term. Our paper not only indicates the adjustment to the crop-livestock system as an adaptation strategy to a severe typhoon, but it also is a warning about the contraction of crops production in the aftermath of this type of event.
Keywords: O12; O13; Q12; Q15; Q54; 330; Typhoon; Agriculture; Crops; Livestock; Vietnam